Structural and electronic determinants of lytic polysaccharide monooxygenase reactivity on polysaccharide substrates. Issue 1 (December 2017) - Simmons, T.; Frandsen, K.; Ciano, L.; Tryfona, T.; Lenfant, N.; Poulsen, J.; Wilson, L.; Tandrup, T.; Tovborg, M.; Schnorr, K.; Johansen, K.; Henrissat, B.; et al.
Abstract Lytic polysaccharide monooxygenases (LPMOs) are industrially important copper-dependent enzymes that oxidatively cleave polysaccharides. Here we present a functional and structural characterization of two closely related AA9-family LPMOs fromLentinus similis (Ls AA9A) andCollariella virescens (Cv AA9A). Ls AA9A andCv AA9A cleave a range of polysaccharides, including cellulose, xyloglucan, mixed-linkage glucan and glucomannan.Ls AA9A additionally cleaves isolated xylan substrates. The structures ofCv AA9A and ofLs AA9A bound to cellulosic and non-cellulosic oligosaccharides provide insight into the molecular determinants of their specificity. Spectroscopic measurements reveal differences in copper co-ordination upon the binding of xylan and glucans.Ls AA9A activity is less sensitive to the reducing agent potential when cleaving xylan, suggesting that distinct catalytic mechanisms exist for xylan and glucan cleavage. Overall, these data show that AA9 LPMOs can display different apparent substrate specificities dependent upon both productive protein–carbohydrate interactions across a binding surface and also electronic considerations at the copper active site. Copper-dependent lytic polysaccharide monooxygenases (LPMOs) oxidatively cleave polysaccharides. Here the authors present a structure-function characterization of fungal LPMOs, showing that a particular LPMO cleaves xylan using a mechanism that involves an alternative copper coordination geometry.